MET Inhibitors for the Treatment of Gastric Cancer: What’s Their Potential? - El Darsa H; El Sayed R; Abdel-Rahman O (Dove Medical Press, 2020)
Haidar El Darsa,1 Rola El Sayed,2 Omar Abdel-Rahman1 1Division of Medical Oncology, Department of Oncology, Cross Cancer Institute, University of Alberta, Edmonton, Alberta, Canada; 2Division of Hematology-Oncology, Department of Internal Medicine, American University of Beirut Medical Center, Beirut, LebanonCorrespondence: Omar Abdel-RahmanDivision of Medical Oncology, Department of Oncology, Cross Cancer Institute, University of Alberta, Edmonton, Alberta, CanadaEmail Omar.Abdelsalam@ahs.caAbstract: Gastric cancer remains a disease with a dismal prognosis. Extensive efforts to find targetable disease drivers in gastric cancer were implemented to improve patient outcomes. Beyond anti-HER2 therapy, MET pathway seems to be culprit of cancer invasiveness with MET-overexpressing tumors having poorer prognosis. Tyrosine kinase inhibitors targeting the HGF/MET pathway were studied in MET-positive gastric cancer, but no substantial benefit was proven. Some patients responded in early phase trials but later developed resistance. Others failed to show any benefit at all. Etiologies of resistance may entail inappropriate patient selection with a lack of MET detection standardization, tumor alternative pathways, variable MET amplification, and genetic variation. Optimizing MET detection techniques and better understanding the MET pathway, as well as tumor bypass mechanisms, are an absolute need to devise means to overcome resistance using targeted therapy alone, or in combination with other synergistic agents to improve outcomes of patients with MET-positive GC.Keywords: gastric cancer, MET over-expression, MET amplification, HGF, tyrosine kinase inhibitors, monoclonal antibodies